Exploring translation accuracy and acceptability in political discourse: a linguistic study of Crown Prince Mohammed bin Salman’s speech - Mohammad Jundurahman Nabilah; Syihabuddin, S; Supriadi, Rinaldi (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2025)
In the era of globalization, translation quality plays a pivotal role in ensuring the accurate and culturally appropriate transfer of messages, particularly in high-stakes diplomatic contexts. This study addresses the urgency of analyzing translation techniques and quality in the Indonesian rendering of Crown Prince Mohammed bin Salman’s speech delivered at the Arab-Islamic Extraordinary Summit in Riyadh. The main objective is to assess the effectiveness of translation techniques in achieving accuracy and acceptability, two critical aspects of translation quality. Employing a qualitative content analysis method, the study scrutinized 30 speech segments drawn from social media video excerpts. Data collection involved expert evaluation by two Arabic language specialists and acceptability assessments from 20 trained student respondents. The analysis revealed that modulation, transposition, and literal translation were the most frequently applied techniques, with modulation and transposition contributing significantly to maintaining message clarity and cultural relevance. Meanwhile, excessive reliance on literal translation occasionally reduced contextual accuracy. The findings underscore the necessity of strategic technique selection to balance fidelity to the source text and naturalness in the target language. This research contributes to the field of translation studies by emphasizing the importance of culturally informed approaches in diplomatic translation and suggests further investigations involving diverse text genres and readability considerations.